167k views
0 votes

A=(1)/(2)\pi w^2+2lw

Solve for L

User Claxton
by
4.5k points

2 Answers

3 votes

Answer:

l = a/(2 w) - (π w)/4

Explanation:

Solve for l:

a = 2 l w + (π w^2)/2

a = 2 l w + (π w^2)/2 is equivalent to 2 l w + (π w^2)/2 = a:

2 l w + (π w^2)/2 = a

Subtract (π w^2)/2 from both sides:

2 l w = a - (π w^2)/2

Divide both sides by 2 w:

Answer: l = a/(2 w) - (π w)/4

User Elias Platek
by
4.2k points
1 vote

Answer:


l=(2A-\pi w^2)/(4w)

Explanation:

Subtract terms not containing L, then divide by its coefficient.


A=(1)/(2)\pi w^2+2lw\\\\A-(1)/(2)\pi w^2=2lw\\\\l=(2A-\pi w^2)/(4w)

User Srividya
by
5.4k points